Affiliate Marketing Business as a Digital Entrepreneurship Model: An Analysis of Opportunities and Challenges in the Creative Economy Era 2025 - Putri Pramesti, Ginna Novarianti Dwi (Worldwide Research Publishing, 2023)
The development of the creative economy in the digital era has opened up new opportunities for technology-based entrepreneurship models, one of which is affiliate marketing. This business model is increasingly popular because it offers flexibility, low capital requirements, and broad market access potential through e-commerce and social media platforms. However, despite its great potential, affiliate marketing practices also face a number of challenges, ranging from limited digital literacy, reliance on platform algorithms, to immature transparency and regulatory issues. Therefore, this research is important to comprehensively analyze the opportunities and challenges of affiliate marketing as a digital entrepreneurship model in supporting the growth of the creative economy in 2025. This study uses a qualitative approach with a descriptive method. Data were collected through in-depth interviews with affiliate marketers, participatory observations, and documentation studies from related literature sources. Data analysis was carried out using the Miles & Huberman interactive model which included data reduction, data presentation, and conclusion drawing through triangulation techniques. The results of the study show that the main opportunities of affiliate marketing include expanding market access, time flexibility, and contributing to financial inclusion, especially for students and MSMEs. However, the challenges found include low digital literacy, instability of platform algorithms, tight competition, and consumer trust issues. This study concludes that affiliate marketing can be a driving force for the creative economy if supported by strategies to strengthen digital literacy, adaptive regulations, collaboration with platforms, and halal product innovation. The implications of this research confirm the importance of multi-stakeholder synergy in building an inclusive and sustainable digital entrepreneurship ecosystem.